Mild Biamidine-Transfer Conditions for the Synthesis of Aliphatic Biguanides - Bardovskyi, Rostyslav; Fabre, Marie; Ronco, Cyril; Benhida, Rachid (SynOpen, 2021)
This study focuses on the development of new synthetic pathways to monosubstituted biguanides from amines. An exhaustive comparison of the conditions and reagents used for biamidine transfer was performed. New reagents were synthesized and optimized conditions for the synthesis of substituted biguanides under mild conditions were developed. Eventually, two high-yielding and straightforward protocols for the transfer of a biamidine group to various amines are proposed and their scope and limitations have been explored. These conditions include: i) a direct chromatography-free procedure and ii) an eco-friendly procedure in water compatible with bioinspired molecules. They are particularly efficient for the demanding conversion of aliphatic amines.
Keywords: biguanide; biamidine transfer; mild conditions; biocompatible protocol; guanidine derivatives